The impact of institutional distance on sustainable investment: evidence from China’s Belt and Road Initiative - Kankanam Pathiranage, Heshan Sameera; Xiao, H.; Li, W. (2020)
Purpose: In an attempt to satisfy the desire to become a global economic leader, China is working on a series of ambitious deals with several countries. As a major country in a region considered as an emerging market, the immense infrastructure gap that is curtailing trade and accessibility for economic growth has led to major changes in economic policy. The past few decades have seen China invest billions of dollars not only in the developing countries of Africa and Asia but also in other world economic giants of Europe and the USA. China has embarked on a rigorous global effort to close the infrastructure gap through the Belt and Road Initiative (BRI) in partnership with multilateral development banks. China’s BRI brings together several countries in East Asia and the Eurasian mainland into close proximity with China, thereby promoting inland trade between the countries. The investments in this project are estimated to reach US$1tn over a span of ten years. However, the volume of outward foreign direct investments (OFDI) from China to the host countries is determined by several factors. Several previous researchers have studied various issues affecting the business activities of China and the given countries. First, the cultural organization, policy approaches and objectives of China as a country create trade barriers with countries involved in the BRI plan. This paper aims to provide a comparative overview of how the institutional distance of the Belt and Road countries from China affects their sustainable development. Design/methodology/approach: Data on the nature, success and challenges of the BRI (such as the volume of bilateral trade and OFDIs and its financial implications) were extracted from various published studies. The impact of cultural distance and internationalization of the BRI enterprise was analyzed through a comparative research methodology. Findings: A significant relationship exists between institutional distance and sustainable development of the Belt and Road countries. However, the barriers – for example, inhospitable culture and regulations for organizations in participating countries – could become pillars of success once resolved. Originality/value: Previous studies lacked a standard framework to investigate how institutional distance is related to China’s outbound trade with the Belt and Road countries. The comparative analysis methodology adopted in this study fills this gap.